2018
DOI: 10.1038/s41467-017-02630-w
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase inhibition upregulates MHC-I to potentiate cytotoxic T lymphocyte responses in breast cancer

Abstract: Potentiating anti-tumor immunity by inducing tumor inflammation and T cell-mediated responses are a promising area of cancer therapy. Immunomodulatory agents that promote these effects function via a wide variety of mechanisms, including upregulation of antigen presentation pathways. Here, we show that major histocompatibility class-I (MHC-I) genes are methylated in human breast cancers, suppressing their expression. Treatment of breast cancer cell lines with a next-generation hypomethylating agent, guadecitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(184 citation statements)
references
References 29 publications
5
179
0
Order By: Relevance
“…Hypomethylating agents, such as Aza, have the potential to meet this need. In gene expression data from breast cancer patients with matched biopsies before and after treatment with Aza and entinostat, the treatment increased the expression of multiple HLA molecules in all five patients (25). If a DNMTi such as Aza were able to increase MHC class I presentation of tumor antigens or IFN-γ responses in human PDAC, it may promote more favorable responses to current immunotherapies that PDAC, in general, has been highly refractive to Pu et al (60).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Hypomethylating agents, such as Aza, have the potential to meet this need. In gene expression data from breast cancer patients with matched biopsies before and after treatment with Aza and entinostat, the treatment increased the expression of multiple HLA molecules in all five patients (25). If a DNMTi such as Aza were able to increase MHC class I presentation of tumor antigens or IFN-γ responses in human PDAC, it may promote more favorable responses to current immunotherapies that PDAC, in general, has been highly refractive to Pu et al (60).…”
Section: Discussionmentioning
confidence: 86%
“…However, the observation that highly immunogenic TEs and TAAs significantly increase during transformation to PDAC, but do not cause a significant anti-tumor response to prevent progression and growth, would suggest that components involved in anti-viral immunity and/or antigen-presentation are compromised during this transition. In fact, recent studies in immunocompetent melanoma, ovarian, colorectal and breast cancer models (14,15,25) have shown that activation (i.e., upregulated expression) of TEs in conjunction with increased, innate type I interferon signaling and MHC class I expression, through DNMTi treatment, sensitizes tumor cells to immune attack, which contributes to dramatically decreased tumor growth. These data would suggest that the benefit of anti-TAA or -TE immunity to control tumor growth outweighs their tumor promoting activity.…”
Section: Upregulation Of Te and Taa Expression In Pdac Coincides Withmentioning
confidence: 99%
See 1 more Smart Citation
“…While the mechanism of action of HMAs in AML is diverse, there is increasing appreciation of immunomodulatory effects in mediating response. In solid tumour models, HMAs exert regulatory effects on the antigen presenting properties of malignant cells (Karpf, 2006;Woloszynska-Read et al, 2008;Akers et al, 2010;Almstedt et al, 2010;Goodyear et al, 2010;Srivastava et al, 2014;Ørskov et al, 2015). Pre-treatment of tumour cells with HMAs primes tumours to induce potent immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…Epigenetic modifiers such as DNA methyltransferase inhibitors and histone deacetylase inhibitors are suitable combination partners because of an enhancement in antigen processing and presentation of malignant cells. [22][23][24][25] In the setting of myelodysplastic syndrome, the combination of vaccination against NY-ESO-1 and decitabine resulted in an increased antigen-specific immune response. 26 In our hands, the combination of next-generation DC vaccination with 5azacytidine resulted in a striking increase in local and systemic immune responses.…”
Section: Discussionmentioning
confidence: 99%